Necrotizing fasciitis of the lower limb: a prospective study of prognostic factors affecting mortality - Chee, E.K.; Kwan, M.K.; Khoo, E.H. (2009)
Necrotizing fasciitis is a life and limb threatening soft tissue infection with a high mortality rate. This study tries to identify the possible risk factors that contribute to mortality in patients with necrotizing fasciitis involving a lower limb. We prospectively reviewed 41 patients that presented with necrotizing fasciitis of the lower limb over a period of one year. Results show that the mortality rate for necrotizing fasciitis of the lower limb is quite high at 19.5. Comparison among necrotizing fasciitis patients reveals that higher mortality rate is seen among those patients with advanced age and those presented with initial high pre-operative creatinine levels. Sex, pre-morbid diabetes mellitus, duration from initial symptoms to presentation for treatment and presence of streptococcus group A were not associated with an increased mortality rate. Neither were admission vital signs, subcutaneous gas on radiograph, prior antibiotic treatment on admission or clinical note of bullae formation.